2016
DOI: 10.1590/1980-5497201600010013
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de antioxidantes em participantes do ELSA-Brasil: resultados da linha de base

Abstract: The greater intake of fruits and vegetables is likely to be involved in the higher consumption of antioxidants in females. General policies to increase the consumption of such nutrients should be directed to groups of lower income, education and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
2
Order By: Relevance
“…The Se RDI for adults is 55 µg/day with a tolerable upper intake level (UL) of 400 µg/day (18). The Se intake values in a cohort of Brazilian adults, the ELSA study, identified a mean intake of 222 µg/day, being higher among women (19). The National Food Survey of the Family Budget Survey (FBS) (2008-2009) identified a mean intake value of 107.61 µg/day in the population, being higher among male adults (20).…”
Section: Introductionmentioning
confidence: 99%
“…The Se RDI for adults is 55 µg/day with a tolerable upper intake level (UL) of 400 µg/day (18). The Se intake values in a cohort of Brazilian adults, the ELSA study, identified a mean intake of 222 µg/day, being higher among women (19). The National Food Survey of the Family Budget Survey (FBS) (2008-2009) identified a mean intake value of 107.61 µg/day in the population, being higher among male adults (20).…”
Section: Introductionmentioning
confidence: 99%
“…Because T2D develops even with low energy intake, it is suggested that the disease is caused by factors other than obesity or overeating. The average daily energy intake varies by country; for example, the average daily energy intake in Brazil is 2855 kcal [ 10 ], whereas in Japan it is 1903 kcal [ 11 ]. It is therefore pertinent to focus on energy intake in studies on T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Este estudo abordou uma temática ainda pouco investigada, considerando o público estudado e a relação entre consumo de micronutrientes antioxidantes e associação com o perfil lipídico destes. Percentuais elevados de inadequação no consumo de micronutrientes pela população brasileira tem sido relatada em estudos atuais (Tureck, et al, 2017;Teixeira, Mill, Pereira & Molina, 2016). Em adolescentes também são relatados percentuais crescentes de inadequação de consumo, justificando os valores observados nesse estudo (Veiga, et al, 2013;IBGE, 2020).…”
Section: Discussionunclassified